Surface computing: The post-PC experience - Hodges, Steve (Microsoft Research, 2008)
Surface computing: The post-PC experience. Slideshow.
Presentation at the UKDL Event on Touch Screen Technology and Interactive Display Technology, Cambridge, UK.